A fogyasztói információforrások megítélése az otc gyógyszerek piacán = Assessment of consumers’ information sources on the otc drug market - Lányi, Beatrix (Közép-Európai Közlemények, 2018)
The complex usage of marketing activity in the healthcare and pharmaceutical industry began to flourish after the 1990s. Since than a dynamic expansion can be observed and it improves parallel to the technology development and to the continuously changing expectations of clients. Pharmaceutical products differ significantly in many aspects from other consumer goods. They satisfy special needs and consumers cannot be considered experts, so besides the rational reasons several emotional and confidential factors influence the buying process and the consumption. Drug promotion denotes to all information and persuasive actions by manufacturers and distributors that result in the evocation of sale and purchase as well as the usage of medication. Consumers’ behaviour in the pharmaceutical market changed notably in the last decade. Today’s consumer feels himself/herself more informed and independent, moreover he or she is hesitant to adapt the traditional model of prescription and monitored medication. In this paper Hungarian non-prescriptive drug industry is analysed from the perspective how customers gain information about OTC drugs.